Behavioral Trust in Competence Versus Morality: Experimental Evidence of Differences and Similarities - Detlef Fetchenhauer; David Dunning; Daniel Ehlebracht; Thomas Graczyk; Thomas Schlösser (Journal of Behavioral Decision Making, 2025)
Life is full of decisions about whether to trust other people. At a cognitive level, people can be skeptical about another person's trustworthiness but are averse to signaling their suspicions at a behavioral level. This phenomenon of “principled trustfulness” has been documented for trust implicating the moral character of another person but not explored for cases involving their competence. We introduce a new game-theoretical paradigm, the competence game, in which participants can bet money on whether an interaction partner will pass an intelligence test, thus placing trust in their partner's competence. Across four studies ( N 0.167em=0.167em3337 participants analyzed, each making a decision to risk), we compared behavior in competence games and traditional trust games, which focus on moral choice and lottery gambles. In competence games, participants were significantly less likely to trust their interaction partner than in trust games even if the pay-off structure and likelihood of reaching a positive outcome were identical. Thus, trust in competence is not as principled to the same degree as trust in moral character but seems to be approached more like a self-interested investment decision.
Keywords: 650; competence; competence game; morality; trust; trust game